Employing in-situ hydrogen peroxide generation to alleviate aquatic impact from methylene blue-contaminated water - Quimada, N. E.; Ogdiman, R. A. (International Journal of Agricultural Technology, 2025)
The accumulation of dyes in aquatic environments poses significant ecological risks, and methylene blue (MB) is one such dye that requires effective removal. This study evaluated the efficiency of an electrolytic system for generating hydrogen peroxide (H₂O₂) to decolorize MB. The process was optimized by examining the effects of pH, applied current, and activated carbon (AC) weight using Response Surface Methodology (RSM). Results indicated a high coefficient of determination (R² = 0.9446), demonstrating the robustness of the predictive model for decolorization. Increasing applied current, oxidation time, and AC weight improved color removal, while lower pH levels enhanced the process, consistent with electro-Fenton principles. The maximum color removal achieved was 57.51% under optimal conditions. Additionally, three hydrogen peroxide production methods—bubbling, electrolysis, and electrolysis with Fe²⁺ addition—were compared. The results showed that while bubbling alone was less effective for color removal, both electrolysis and electrolysis with Fe²⁺ significantly increased color removal, with electrolysis and Fe²⁺ addition proving to be the most effective method. This study highlights the potential of an electrolytic system for efficient dye decolorization, offering a promising solution for treating dye-contaminated water.